2012
DOI: 10.1038/leu.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular effects of oncogene cooperation in a genetically accurate AML mouse model

Abstract: Biallelic CEBPA mutations and FMS-like tyrosine kinase receptor 3 (FLT3) length mutations are frequently identified in human acute myeloid leukemia (AML) with normal cytogenetics. However, the molecular and cellular mechanisms of oncogene cooperation remain unclear because of a lack of disease models. We have generated an AML mouse model using knockin mouse strains to study cooperation of an internal tandem duplication (ITD) mutation in the Flt3 gene with commonly observed CCAAT/enhancer binding protein alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Specifically, these groups applied genetic models to uncover the important role of CEBPA for granulocytic lineage commitment and differentiation, as well as the causative role for mutant CEBPA in AML, thereby dissecting the complexity of how biallelic CEBPA mutations contribute to leukemogenesis. 23,24 …”
Section: European Research Contributionsmentioning
confidence: 99%
“…Specifically, these groups applied genetic models to uncover the important role of CEBPA for granulocytic lineage commitment and differentiation, as well as the causative role for mutant CEBPA in AML, thereby dissecting the complexity of how biallelic CEBPA mutations contribute to leukemogenesis. 23,24 …”
Section: European Research Contributionsmentioning
confidence: 99%
“…[4][5][6] Clinical observations and experimental studies have shown that FLT3-ITD can co-operate strongly in leukemia induction with a variety of leukemia-initiating gene fusions such as MLL-AF9, MLL-GAS7, AML1-ETO, PML-RARα or NUP98-HOXD13. [7][8][9][10][11][12][13] Several studies have shown that FLT3-ITD alone can cause a myeloproliferative disorder in mice, but is not sufficient to induce AML. [14][15][16] NUP98-NSD1 is the product of a cytogenetically silent chromosomal translocation t(5;11) (q35;p15.5) that generates a fusion between the N-terminus of nucleoporin 98 (NUP98) and the C-terminal part of the nuclear receptor-binding SETdomain-containing protein NSD1.…”
Section: Introductionmentioning
confidence: 99%
“…Knock-in mouse models have been instrumental in deciphering the hematopoietic and leukemogenic effects of FLT3-ITD alone [4][5][6] and in combination with mutations co-occurring with FLT3-ITD in human AML [7][8][9][10][11][12] ; as well as in studying the effectiveness of different therapeutic approaches in FLT3-ITD-positive leukemias. F692L), was present at allele frequencies of 0.55-0.94.…”
mentioning
confidence: 99%